2021
DOI: 10.1016/j.bodyim.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Do you see what I see? The influence of self-objectification on appearance anxiety, intrinsic motivation, interoceptive awareness, and physical performance

Abstract: Objectification theory suggests that when individuals take on an observer's perspective of their physical appearance (known as self-objectification), they experience an increase in body shame and anxiety and a decrease in motivation and bodily awareness. The purpose of this study was to determine if self-objectification could impact social physique anxiety, intrinsic motivation, and bodily awareness as well as physical performance.Undergraduate female students (N=54) were recruited to participate in a Consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 96 publications
(190 reference statements)
1
16
0
Order By: Relevance
“…According to the general theoretical model proposed for university students, it is observed that when physical-sports practice is oriented towards the ego climate, positive relationships are observed between both variables; however, when it is oriented towards the task climate, a decrease in the levels of this disruptive state is fostered. Similar results were obtained by Castro-Sánchez et al (2019) where they state that when a sport is carried out professionally, anxiety levels increase due to the high degree of competitiveness, nevertheless, Dimas et al (2021) argue that when the practice of physical exercise is oriented towards fun and maintaining a non-sedentary lifestyle, there is a decrease in anxiety levels, attributing this effect to the secretion of neurotransmitters such as serotonin and dopamine (Ubago-Jiménez et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…According to the general theoretical model proposed for university students, it is observed that when physical-sports practice is oriented towards the ego climate, positive relationships are observed between both variables; however, when it is oriented towards the task climate, a decrease in the levels of this disruptive state is fostered. Similar results were obtained by Castro-Sánchez et al (2019) where they state that when a sport is carried out professionally, anxiety levels increase due to the high degree of competitiveness, nevertheless, Dimas et al (2021) argue that when the practice of physical exercise is oriented towards fun and maintaining a non-sedentary lifestyle, there is a decrease in anxiety levels, attributing this effect to the secretion of neurotransmitters such as serotonin and dopamine (Ubago-Jiménez et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…As described, self-esteem seems to be related to affective responses, so people with higher levels of self-esteem may feel this due to an increase in positive activation [ 22 , 31 , 69 ]. Intrinsic motives, when connected with positive activations, offer a better understanding of self-esteem, particularly in women [ 70 ]. This should lead exercise physiologists not only to understand the reasons why women engage in regular exercise, but also creating conditions for them to sense positive activations [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The celebrities in the media make people pay more attention to their bodies [ 28 ]. Self-objectification is positively correlated with appearance anxiety [ 44 , 45 ]. People with high levels of self-objectification were more likely to compare their appearance to others [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%